From images to voices: A photo analysis of medical and social support needs of people living with HIV/AIDS in Tanzania - William N Mkanta; Rosemary W Eustace; Michelle C Reece; Abeer D Alamri; Trevor Davis; Emmanuel U Ezekekwu; Aishwarya Potluri (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background Tanzania is one of the countries hardest hit by HIV/AIDS in Sub-Saharan Africa. Since early 1980s, different levels of community interventions have been designed to provide care and address challenges faced by people living with HIV/AIDS (PLWHA). These efforts are of little value, however, if they lack the opinion of PLWHA on their needs. We used photographs taken and selected by PLWHA to identify perceived needs and challenges related to daily living with the disease. # Methods A qualitative, cross-sectional study using the Photovoice method was conducted to assess the perceptions of PLWHA relative to service needs associated with HIV care. # Results Through the content analysis method, PLWHA needs were generated based on major categories of *financial resources*, *psychological support*, *cultural competency* and *patient empowerment and engagement* in HIV care and services. # Conclusion This study generated information that could be useful in promoting increased awareness of PLWHAs' service needs to the local and global communities. Of particular importance is the policy implication geared towards promoting advocacy with meaningful inclusion of the opinion of PLWHA in designing, delivery, and monitoring of HIV/AIDS-related social and health services.